Rekam Gigi Sebagai Alat Identifikasi Dan Pembuktian Hukum Di Pengadilan - Soepriadi; Anggraeni Endah Kusumaningrum (Badan Penerbit STIEPARI Press, 2022)
Everyone has an identity to distinguish them from others. This identity has a legal aspect. The most important, simple and immediate anticipation of these things is to fix or make a Dental Medical Record in this case a good, complete, uniform, and easy to understand odontogram, both by the medical community, paramedics, law enforcers, as well as ordinary people, using universally applicable standards (national and international). This study uses a normative juridical approach, with qualitative descriptive analysis. Odontogram medical records are indispensable as an identification tool in accordance with the Law on Medical Practices of 2004 and the Minister of Health Regulation of the Republic of Indonesia 269/Menkes/Per/2008. In the implementation of medical practice, every doctor and dentist must refer to the applicable standards, guidelines and procedures so that the public gets professional and safe medical services and can avoid legal problems. As a medical record, the odontogram can be used as evidence in court because it is categorized as evidence for expert testimony as stated in the Minister of Health Regulation No. 269/2008 article 13 states that medical records have benefits, namely evidence in the law enforcement process, medical and dental disciplines in the enforcement of medical ethics and dental ethics.